Fuerza de rotura y tiempo óptimo de cocción de pastas elaboradas con harina de trigo - almidón fruta pan. - Buele Paredes, Mayra Marilyn (2017)
Food pasta semolina is a traditional food and widely accepted due to its nutritional qualities and important source of carbohydrates, low in protein. Given the deficiency of lysine in wheat protein, wheat semolina is supplemented with starch of native breadfruit (Artocarpus altitis), as a result, the quality of the food paste is improved because the starch is an elastic fluid, structured tenacity with gelling properties, swelling factor and water retention capacity. Considering these acceptable rheological characteristics, it is intended to change the productive matrix and food sovereignty, taking advantage of the own resources of Pasaje-El Oro province, in this case, botanical sources rich in breadfruit starch (Artocarpus altitis), contribute to maintain of the mechanical conditions and sensorial attributes of traditional pasta. The objective of the present work was to evaluate the breaking strength and optimal cooking time of fusilli pasta made of the partial substitution of wheat flour (Triticum durum) instead of native breadfruit starch (Artocarpus altitis). Considering these substitutions do not affect widely the sensorial attributes of the compound pasta. Three treatments of partial substitution of wheat flour (Triticum durum) by native starch of breadfruit (Artocarpus altitis) in distributive proportions were evaluated: T1 (90-10), T2 (80-20) and T3 (70-30), Matched to standard sample T0 (100-0), respectively. The breaking force in fusilli pasta was evaluated using the texturometry method and was determined by using the Brookfield ProCT3 Texturometer with the TA39 probe which is a computerized texture analyzer that mimics two or more chewing cycles by compressing the sample. The other objective of this investigation is to determine the optimal cooking time of fusilli pasta. It was carried out using the traditional method of boiling water until it was possible to verify the presence of the visible white line in the center of the pasta, known as "Al Dente" visible when pressing the fusilli type pasta with the compression plates. 27% yield of native starch of breadfruit (Artocarpus altitis) was obtained, breadfruit seeds were presented in lower values compared to wheat, this one has a yield with 60% to 70% percentage, ideal measure for the elaboration of Compound pastes. According to the results, the breaking strength and optimum cooking time of fusilli pasta using partial substitution mixtures of wheat flour (Triticum durum) and native breadfruit starch (Artocarpus altitis), show values were significantly affected (p≤0.05) to the control sample from the 30% substitution due to preliminary tests that showed that an incorporation over this percentage in the elaboration of fusilli pasta requiring the sensory attributes to traditional pasta.